La " défense du territoire " en Italie du Nord, ou le détournement des formes de la participation locale - Dematteo, Lynda (Anthropologica, 2022)
The separatism of the Northern League is rooted in the Catholic intransigence of the Lower Alpine provinces of northern Italy. It is the fruit of a prepolitical communitarianism which entails the rejection of the nation and foreigners on the basis of ethnicization of territory. The Northern League proposes "to preserve" local communities from the intrusion of the central government and outsiders and assuage the security concerns that emerge in down-at-heel peripheral districts using the vocabulary of order and cleanliness instead of that of racism. This article examines three situations in Bergamo which demonstrate the re-emergence of local manifestations of the prepolitical and illustrate the populist distraction of participatory rhetoric. The first is a case of reconquering public spaces occupied by foreigners; the second concerns restoring a moral order threatened on all sides; and, the third involves privileging the resolution of local difficulties in order to restore an idealized traditional community.